1995
DOI: 10.1038/376594a0
|View full text |Cite
|
Sign up to set email alerts
|

An IL-12-based vaccination method for preventing fibrosis induced by schistosome infection

Abstract: The harmful fibrosis which often occurs in the context of infectious disease involves the excessive deposition of connective tissue matrix, particularly collagen, and is mostly resistant to pharmacological and immunological intervention. In schistosomiasis, fibrosis is associated with the granulomatous response to parasite eggs trapped in the liver. We have previously shown that interleukin (IL)-12 administered peritoneally with eggs prevents subsequent pulmonary granuloma formation on intravenous challenge wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
296
2

Year Published

1997
1997
2010
2010

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 388 publications
(320 citation statements)
references
References 23 publications
22
296
2
Order By: Relevance
“…This finding is particularly interesting in light of the potent downregulatory effect of IL-12 on the development of S. mansoni egg-induced granulomatous responses. 49,68,69 However, these findings are somewhat tempered by recent findings from Stat-4Ϫ/Ϫ mice, which lack IL-12-mediated immune responses, 70 in which pulmonary granuloma formation was modestly inhibited during S. mansoni infection. 16 Regardless of the precise role invoked by Th1-type cytokines during S. mansoni egg granuloma formation, it was apparent from the present study that IL13-PE treatment did not appear to promote an aggressive Th1 cytokine response as a result of its diminution of the Th2 cytokine response.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is particularly interesting in light of the potent downregulatory effect of IL-12 on the development of S. mansoni egg-induced granulomatous responses. 49,68,69 However, these findings are somewhat tempered by recent findings from Stat-4Ϫ/Ϫ mice, which lack IL-12-mediated immune responses, 70 in which pulmonary granuloma formation was modestly inhibited during S. mansoni infection. 16 Regardless of the precise role invoked by Th1-type cytokines during S. mansoni egg granuloma formation, it was apparent from the present study that IL13-PE treatment did not appear to promote an aggressive Th1 cytokine response as a result of its diminution of the Th2 cytokine response.…”
Section: Discussionmentioning
confidence: 99%
“…Stat4 deficient mice showed a minimal Th1 response but normal hepatic granulomas. Wynn et al (1995a) found that immunization with SEA and IL-12 produced immune deviation toward Th-1 type reactions with reduction of granuloma sized. All of these effects are consistent with the concept of the granuloma as a Th2 dominant reaction, but under some conditions Th1 granulomatous responses may be predominant and damaging , Chen & Boros 1999, Hoffmann et al 2000, Rutitzkky et al 2001.…”
Section: The Role Of Cytokines In Granuloma Formation and Downregulatmentioning
confidence: 95%
“…Immunological studies of the adaptive immune response in the mouse have focused on the prevalent CD4 + T cell activity and revealed that, initially, the host develops a Th1 response, which is characterized by the production of IFN-c. However, as the infection progresses, this Th1 response gradually succumbs to a dominant Th2 response, and is indicated by the secretion of IL-4, IL-5, IL-13 and IL-10 [2][3][4][5]. The host factors that are responsible for the initial Ag-specific Th1 response remain unclear.…”
Section: Introductionmentioning
confidence: 99%